2013
DOI: 10.1016/j.celrep.2013.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Neuraminidase-Mediated, NKp46-Dependent Immune-Evasion Mechanism of Influenza Viruses

Abstract: Natural killer (NK) cells play an essential role in the defense against influenza virus, one of the deadliest respiratory viruses known today. The NKp46 receptor, expressed by NK cells, is critical for controlling influenza infections, as influenza-virus-infected cells are eliminated through the recognition of the viral hemagglutinin (HA) protein by NKp46. Here, we describe an immune-evasion mechanism of influenza viruses that is mediated by the neuraminidase (NA) protein. By using various NA blockers, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
63
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 21 publications
(31 reference statements)
4
63
0
Order By: Relevance
“…IgG fusion proteins containing the extracellular domain of NKG2D, NKp30, NKp44, or NKp46 were prepared and used for FACS staining of infected or uninfected SupT1 cells as previously described (35 At the indicated time points, cells were stained with anti-ULBP1, anti-ULBP2, anti-ULBP3, anti-MICA, anti-MICB, and anti-B7-H6 antibodies (all obtained from R&D Systems) as well as the mouse isotype IgG2b antibody (BioLegend). Anti-CD48 was obtained from Santa Cruz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IgG fusion proteins containing the extracellular domain of NKG2D, NKp30, NKp44, or NKp46 were prepared and used for FACS staining of infected or uninfected SupT1 cells as previously described (35 At the indicated time points, cells were stained with anti-ULBP1, anti-ULBP2, anti-ULBP3, anti-MICA, anti-MICB, and anti-B7-H6 antibodies (all obtained from R&D Systems) as well as the mouse isotype IgG2b antibody (BioLegend). Anti-CD48 was obtained from Santa Cruz.…”
Section: Methodsmentioning
confidence: 99%
“…The inhibitory signal is mostly dependent on the recognition of MHC class I on target cells by appropriate NK inhibitory receptors (29,30). NK cells also possess numerous activating receptors that are able to recognize stressinduced self-ligands via the receptor NKG2D (31), immune regulatory self-molecules (for instance, the recognition of B7-H6 by the NKp30 receptor [32] or of CD48 by the 2B4 receptor [33]), or viral ligands such as the influenza virus-derived hemagglutinin that is recognized by both the NKp46 and NKp44 receptors (34,35). We and other groups have described several diverse viral mechanisms that manipulate cellular ligands for NK cells to escape the immune system (34,(36)(37)(38)(39)(40)(41)(42)(43)(44); however, knowledge about the interaction of HHV-6-infected cells with NK cells is currently missing.…”
mentioning
confidence: 99%
“…3F). To confirm that the HA Ig staining of the various Ncr1 proteins is specific, we generated fusion proteins of human NKp46, NKp44 (that were shown to bind viral HA) (20,22,25,38,39), and KIR2DL1. We then ran these proteins on SDS-PAGE gels (Fig.…”
Section: Ncr1-noe´is Activated Upon Tumor and Influenza Virus Recognimentioning
confidence: 99%
“…Using the Ncr1 gfp/gfp mice, it was revealed that Ncr1 is involved in controlling influenza virus infections (5,22,25), tumor and metastases eradication (6,7,10,24), the development of type I and type II diabetes (11,23,26,27), liver fibrosis (28), and bacterial infections (3,29). In all of these studies, the activity of the Ncr1 gfp/gfp NK cells was impaired in an Ncr1-dependent manner.…”
mentioning
confidence: 99%
“…NK cells are known mostly for their role in controlling viral infections (20,21) and have been shown to be involved in cytomegalovirus (CMV) (22)(23)(24), influenza virus (6,(25)(26)(27)(28), Newcastle disease virus (29), vaccinia virus (30), and human metapneumovirus (HMPV) infections (31,32). NK cells express a large repertoire of inhibitory receptors, which mostly recognize major histocompatibility complex class I (MHC-I) molecules (missing self hypothesis [33]).…”
mentioning
confidence: 99%